2016
DOI: 10.1136/annrheumdis-2016-209768
|View full text |Cite
|
Sign up to set email alerts
|

The European Scleroderma Trials and Research group (EUSTAR) task force for the development of revised activity criteria for systemic sclerosis: derivation and validation of a preliminarily revised EUSTAR activity index

Abstract: A preliminarily revised SSc activity index has been developed and validated, providing a valuable tool for clinical practice and observational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
149
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 33 publications
4
149
1
1
Order By: Relevance
“…Microvascular dysfunction is a key pathophysiology of SSc . Since at an early stage without internal organ manifestation the disease process is potentially reversible under drug treatment , assessment of the microvascular dysfunction is crucial for individual patient management. However, monitoring of disease activity is still a major challenge for several reasons: First, SSc is a heterogeneous disorder with a high inter‐individual variation regarding disease burden, activity and course .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Microvascular dysfunction is a key pathophysiology of SSc . Since at an early stage without internal organ manifestation the disease process is potentially reversible under drug treatment , assessment of the microvascular dysfunction is crucial for individual patient management. However, monitoring of disease activity is still a major challenge for several reasons: First, SSc is a heterogeneous disorder with a high inter‐individual variation regarding disease burden, activity and course .…”
Section: Discussionsupporting
confidence: 93%
“…A minimum of two of the following criteria were mandatory for disease activity to be classified as “active/progressive” disease: worsening of (1) skin involvement, (2) DUs, (3) CRP elevation (>1 mg/dL), and (4) pulmonary symptoms (progressive fibrosis or reduced diffusion capacity) within the past month. In addition, all patients with active disease identified by the use of these 4 criteria would also be classified as active disease as defined by the revised SSc activity index . The study protocol was reviewed by the local ethics committee (Protocol No.…”
Section: Methodsmentioning
confidence: 99%
“…Patients did not receive any disease-modifying antirheumatic drug treatment at the time of biopsy. Active disease was defined according to the European Scleroderma Trials and Research group (EUSTAR) criteria for disease activity 20. Twenty age-matched and sex-matched healthy volunteers served as controls.…”
Section: Methodsmentioning
confidence: 99%
“…EULAR Scleroderma Trials and Research Group investigators recently identified and validated a new activity index that performs better than the previous ESSG activity index used in this study and in the previous one [27]. A study has just been set up in our centres to investigate the relationships between the NEMO score and the revised activity index.…”
Section: Discussionmentioning
confidence: 99%